PENGUATAN SIFAT MEKANIK KAYU KELAPA SAWIT DENGAN TEKNIK IMPREGNASI REAKTIF MONOMER STIRENA - M. Said Siregar - (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2011)
AbstractThe impregnation technic can be done to improve the quality of palm wood. The dried palm wood specimens were impregnated with styrene monomer and heated at 120°C for 30 minutes. The physical and mechanical properties of impregnated palm wood improved. The outer of palm wood and sixth metres high which impregnated with styrene 20% were the best physical and mechanical properties. The specimen be long to wood classification III ( Indonesian National Standard, SNI 033527-1994).Keywords: palm wood, mechanical properties, impregnation, styrene.